Pemanfaatan ekstrak bunga telang (Clitoria ternatea Linn) sebagai pewarna alami pada minuman bersoda - Syifa Unawahi; Asri Widyasanti; Souvia Rahimah (AGROINTEK, 2022)
Soft drinks are carbonated drinks that are popular among people because providing a refreshing taste when consumed. Attractive colors in soft drinks are the main attraction for consumers. Anthocyanin compounds from telang flowers are one of the natural colors that have no negative effects on the body. The application of anthocyanin compounds in soft drinks that have an acidic pH can also maintain the stability of the anthocyanins of telang flowers. This research was conducted to investigate the potential use of telang flower extract as a natural colorant in soft drinks. The extraction method used was an ultrasonic-assisted extraction method using distilled water with the addition of 0.05 % acetic acid. Extraction conditions  was performed with a ratio of 0.02 (w/v); extraction time 90 minutes; and 65 % amplitude. The results of the study showed that the telang flower extract has the potential as a natural colorant in soft drinks. The addition of telang flower extract to colorless soft drinks could produce a more attractive color, namely blue-purple, with a lightness of L* 16.42; redness color intensity a* 25.77; yellowness color intensity b* -41.59; chroma 48.93; and the pH value 4.8, respectively. At refrigerator temperature storage (4-5 °C), the optimal beverage storage technique indicates a color change that was close to stable.